Swing to bop : an oral history of the transition in jazz in the 1940s - Gitler, Ira (Oxford University Press, 1987)
More than fifty major figures in jazz preserve for posterity their recollections of how jazz moved from the big band era in the late 1930s and 1940s into the modern jazz period.